Stock assessment and overexploitation risk of small pelagic fish in fisheries management area 715 of Indonesia - Franklin, Erik C. (2024)
This study presents updated stock assessments and risk analyses of overexploitation for the aggregate small pelagic fish complex and the dominant genus of the complex, Decapterus, for improving the management of the small pelagic fishery in Fisheries Management Area (FMA) 715. The analyses herein used non-equilibrium biomass dynamics models with available data on annual catch and catch per unit effort for 2005 to 2016. Fishing effort was standardised into the number of 20-meter length overall purse-seine vessels. The analyses show that the maximum sustainable yield (MSY) of the aggregate fish was about 121,600 tonnes, caught by 876 purse-seiners, while the MSY of the mackerel scad, Decapterus macarellus (Cuvier, 1833), was about 67,900 tonnes, caught by 805 purse-seiners. Since the mackerel scad and the aggregate fish stocks have been overexploited, a rebuilding strategy would be necessary to restore the stocks to a level capable of producing MSY (BMSY). After achieving the BMSY, it is recommended that a target reference point be implemented for the catch level with the maximum overexploitation risk level of 50 % in 10 years. The catch level meeting this requirement for mackerel scad would equal 80 % of its MSY, which could be achieved by controlling fishing effort at 427 purse-seiners. At this effort level, the fishery would produce 95,800 tonnes of aggregate fish catch with 54,300 tonnes of mackerel scad. These reductions in fishing efforts will be needed to maintain the future sustainability of the fish stocks in FMA 715.